279 Using infographics and video to prevent injuries and illnesses in athletics. (3rd March 2020) - Edouard, Pascal; Branco, Pedro; Glover, Danny; Duncan, Jennifer; Richardson, Andy; Kiss, Marianna; Depiesse, Frederic; Murray, Andrew
Abstract : Background: Injuries and illnesses represent a health problem affecting athletics athletes' training and performance. Recently, research on injury and illness epidemiology and risk factors have provided some insights to help implement prevention strategies. The next step is presenting the science, in an engaging form that can assist medical teams, coaches and athletes understand and implement these strategies. Objectives: To produce resources in order to disseminate knowledge on injuries and illnesses epidemiology and risk factors, and highlight potential prevention strategies. Participants: Researchers and practitioners working in athletics injury and illness prevention collaborated with athletes. Main outcome measurements: Resources/communication assets, for example infographics, animations, video, were produced and shared with medical teams, athletes and coaches. Results: Infographics, animation and engaging knowledge translation tools/educational materials on illness epidemiology during international athletics championships were produced. These took the scientific knowledge, made it specific for the context of athletics, and provided easily digestible, visually rich information. These were shared with athletes at events such as the European Athletics Indoor Championships. Conclusions: We developed resources to be shared to all stakeholders working with athletics athletes, providing tips and practical recommendations on injury and illness prevention. Having share these to athletes and their teams, the next step is to evaluate the documents and tools for and by athletes and involved actors, and the effectiveness of these interventions. These strategies may be relevant to provide athletes with engaging information on preventing injury and illness in other sports.